Refletindo sobre a formação do conceito de número racional na forma fracionária - Demartini, Idite Terezinha (2009)
This work, involving students of a state school from the city of Passo Fundo RS, aimed to check up the formation of the concept of rational number in fractional form at a fifth grade elementary school and, mainly, to identify the difficulties that students face in formation of the concepts of fractions by applying a diagnostic tool in two different moments. In possession of the collected data, which demonstrated some of the students‟ difficulties in forming the concepts and also with the operations with fractions, there were made some activities. These activities aimed to provide the proper learning ambient, which would encourage the formation of the concept of fractional rational number by developing the capacity to interpret, to compare, to analyze, to abstract and to generalize. The analysis of the second moment in the application of the diagnostic tool showed some indicatives of progress about the formation of the concept, but also the resistance of some difficulties in operations, especially between fractions with different denominators. The research questions of this work, that is, what and how to teach order to obtain a more successful cognation in formation of the concept of fraction emphasizes the importance reflection of own practice in construction‟s process of new knowledge. Vigotsky, D‟Ambrosio, André, Perrenoud, Nunes, among others, are the theoretical base, together with other authors that address the teaching-learning process of rational number in fractional form. This investigation showed some potential as: the dialog; the didactic contract established; the playfully and the use of the equivalence of fractions in operations, and weaknesses as: to emphasize the continuous and discontinuous quantities in relation part-whole; no further of meanings about quotient fractions and multiplicative operator and the absence of technological features in development of the proposal. Through this work, we find also that is necessary to address the teaching of fractions with different meanings as quotient, measure, number and multiplicative operator with varied situations and complexity degree, looking for the knowledge that the students have about the theme and contemplating different daily situations, which enable them assign meaning to the different ideas involving the concept of fraction